Juvenile Court Statistics, 1986: Reported Cases in Calendar Year Data Base ([Verlag nicht ermittelbar], 1992)
This data collection describes in quantitative terms the volume of juvenile cases disposed by courts having jurisdiction over juvenile matters (delinquency, status, and dependency cases). Inaugurated in 1926 to furnish an index of the problems brought before the juvenile courts, this series is the oldest continuous source of information on the processing of delinquent and dependent youth done by juvenile courts. Information is provided on state, county, number of delinquency cases by sex, number of status cases by sex, number of dependency cases by sex, and total number of cases by sex.